2015
DOI: 10.3402/meo.v20.27924
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among self-care, dispositional mindfulness, and psychological distress in medical students

Abstract: BackgroundPast research suggests that medical students experience high levels of psychological distress.ObjectiveThe aim of the current study was to investigate the relationships among engagement in self-care behaviours, dispositional mindfulness, and psychological distress.MethodsThe sample consisted of 139 female and 68 male Australian medical students (N=207) aged 17–41 years (M=21.82, SD=3.62) across the 5 years of the Monash University medical course. Participants completed an online survey comprising a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
66
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 42 publications
16
66
1
4
Order By: Relevance
“…Há relato da implantação, com sucesso, de técnicas de relaxamento e massagens, melhora da autoestima e formas de lidar com estresse que parecem estar relacionadas à melhora no bem-estar do estudante de Medicina (Ranjbarkohn & Sajadinejad, 2010;Rong, Glozier, & Luscombe, 2011;Slonim, Kienhuis, Di Benedetto, & Reece, 2015;Velayudhan & Gayatridevi, 2010).…”
Section: Análiseunclassified
“…Há relato da implantação, com sucesso, de técnicas de relaxamento e massagens, melhora da autoestima e formas de lidar com estresse que parecem estar relacionadas à melhora no bem-estar do estudante de Medicina (Ranjbarkohn & Sajadinejad, 2010;Rong, Glozier, & Luscombe, 2011;Slonim, Kienhuis, Di Benedetto, & Reece, 2015;Velayudhan & Gayatridevi, 2010).…”
Section: Análiseunclassified
“…(19) At Monash University, we found that for our students it is associated with significantly enhanced student mental health even during high-stress assessment periods of the semester (20), and greater self-care. (21) Studies have shown that mindfulness can improve memory and learning in university students (22) and help them to cope with exam anxiety. (23) It also seems to improve mental flexibility and problem-solving, (24) as well as reducing clinical errors, and the cognitive biases commonly found behind diagnostic errors.…”
Section: Mindfulness For Training the Medical Student And Practitionermentioning
confidence: 99%
“…Ybarra Sargarduy (2011) en un estudio titulado "Salud Mental y Estilos de Vida en Estudiantes Universitarios" sostiene que uno de cada cinco alumnos universitarios participantes, presenta alteraciones de salud mental; el consumo de tabaco y/o drogas, aparece como un factor de riesgo en las alteraciones de la salud mental, mientras que la actividad física, destaca como un factor de protección 32 . Jessica Slonim y colaboradores (2015), sostuvo que el cuidado de uno mismo en dimensiones como: salud, actividad física, nutrición, espiritualidad, entre otros; potencian el bienestar mental y disminuyen la angustia 33 . La tabla 1, muestra los 19 artículos con resultados de investigación en estilos de vida; destacándose la procedencia, las fortalezas y las debilidades de cada uno.…”
Section: Bienestar Mental Como Determinante Para Un Estilo De Vida Saunclassified
“…The relationships among self-care, dispositional mindfulness, and psychological distress in medical students 33 .…”
Section: Colombia 2014mentioning
confidence: 99%